Synergetic Effect of Bimetallic Au-Ru/TiO2 Catalysts for Complete Oxidation of Methanol - Calzada, Lina (2017)
Bimetallic Ru-Au/TiO2 catalysts prepared by deposition-precipitation with urea method were tested for the first time in the total oxidation of methanol. Different Ru:Au atomic ratios were used (1:1–0.25:1). The catalytic activity results showed a synergetic effect at low temperature (RT–50 °C), mainly for the 1:1 and 0.75:1 atomic ratio. HAADF-STEM and STEM-EDS characterization confirmed the interaction between Ru and Au. TPR, UV–vis spectra, XPS and DRIFTS-CO results also confirm this interaction. FTIR spectra, recorded following the oxidation of methanol as a function of the reaction temperature, showed that formates are the main reaction intermediates in the oxidation of methanol, which are formed from RT on bimetallic Ru-Au catalysts and are oxidized at lower temperatures compared to their monometallic Ru and Au counterparts.